Antifungal activity of the essential oil isolated from Laurus nobilis L. against Cryptococcus neoformans strains - Lílian Sousa Pinheiro, Abrahão Alves de Oliveira Filho, Felipe Queiroga Sarmento Guerra, Camilla Pinheiro de Menezes, Socrates Golzio dos Santos, Janiere Pereira de Sousa, Tassiana Barbosa Dantas , Edeltrudes de Oliveira Lima (Journal of Applied Pharmaceutical Science, 2017)
Cryptococcosis is an opportunistic fungal infection that evolved to an important cause of morbidity and mortality in recent years. Even with advances in medicine, the treatment of ringworm still presents a therapeutic system with limited availability of antifungal agents, and so, research is needed to identify new agents fungistatic or fungicides effectives. The natural products are known to represent an arsenal of compounds, some with antifungal properties. Thus, this study aimed investigates the antifungal activity in vitro of the essential oil of Laurus nobilis L. (leaves) against Cryptococcus neoformans strains. The chemical composition of the oil was analyzed by gas chromatography coupled to mass spectrometry (GC / MS) and minimum inhibitory concentration (MIC) and the minimum fungicidal concentration (MFC) were determined by the broth micro dilution techniques. The MIC100 of essential oil were 256 ðœ‡g/mL and the MFC50 was 1024ðœ‡g/mL. In conclusion the essential oil showed in vitro antifungal potential against strains of C. neoformans.
Keywords: Essential oil,antifungal,Cryptococcus,Laurus nobilis.